Trial by Fire: On the Terminology and Methods Used in Pyrogenic Organic Carbon Research - Zimmerman, Andrew R.; Mitra, Siddhartha (Frontiers in Earth Science, 2017)
Our understanding of the cycling of fire-derived, i.e. pyrogenic organic matter (pyOM), as well as the goals of the community of researchers who study it, may be inhibited by the many terms and methods currently used in its quantification and characterization. Terms currently used for pyOM have evolved by convention, but are often poorly defined. Further, each of the different methods now used to quantify solid and dissolved pyrogenic carbon (pyC) comes with its own biases and artifacts. That is, each detects only a fraction of the total pyrogenic products produced by fire, while, at the same time, include some fraction of non-pyrogenic OM. This may be evident in the commonly observed correlations between pyC and total organic C reported for both soils and dissolved OM in many different systems. We suggest that our research area can be placed on a stronger footing by: 1) agreement upon a common set of terms tied to the method used for detection (e.g. of the form pyCmethod), 2) implementation of another ‘ring trial’ study with a wider set of natural soil and water samples that cross-compare more recently developed methods, and 3) further investigation of the processes which preserve/degrade/transport pyOM in the environment.